Nature Inspired Computation, its Applications and Some Future Directions - Mukesh Kumar Gupta, Dr. Brijesh Kumar (International Journal of Advanced Science and Technology, 2020)
Natural computing presents an overview of significant some new experiments and opportunities to understand various types of models. Natural computing also offers analysis the complex type of the physio- and chemio- and biology based artificial and man-made created problems and solutions in our eco-system. The vast development in the last twenty years have been the emergence in the field of natural inspired computing intelligence consisting mainly of the few fields of fuzzy logic, reinforcement learning, deep learning, Swarm Intelligence, cellular automata, genetic algorithms and evolutionary robotics. This paper refers to investigations, theory-motivated nature inspired based algorithm engineering and also the real-world applications of nature inspired algorithms.